Membangun Sikap Toleransi Beragama dalam Masyarakat Plural - Casram Casram (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
The reality of social life is possible because of accommodating differences and diversities among human being. One of these diversities related to the choice of the faith, and therefore, we should be able to getting along either with the members of the same religious community as well as with those of others. In this case, religious tolerance is a necessity to guarantee social stability against the unwanted ideological force and even physical collisions in the society. Social and religious lives are not to be isolated from each other, but must be integrated into one another. Building educated and open minded religious community is a requirement to achieve this goal. The ideal religious tolerance should be built trough active participation from all members of diverse religious communities to achieve the same goals based on togetherness, inclusive attitude, respect and mutual understanding related to performing certain rituals and doctrins of each religions. The variety of typologies of interfaith relations, such as exclusivism, inclusivisme, pluralism, ect., are commonly formulated to bring these diversities into further step of harmonious religious dialogues. This article reminds us that our comprehension and implementation of religious doctrines should not stop in the claim of exclucivism (“I”) which culminate in realizing personal relationship with God (solitary), nor in the claim of inclusivism (“You”) with its concern with recruiting theological and ideological allies (solidarity), but also in the openness (“We”) where our religious comprehension of human values get emphasized (humanist-functional). In addition, all parties should suspend such a judgment as theological or ideological one directed to other religious community. This is a kind of phenomenological epoché we need to take if we wish to put religious tolerance into practice and not let it stay only on discourse level